Peran Intranet Dalam Membangun Kolaborasi Efektif Di Pelayanan Kesehatan - Hendri Andrian; Vip Paramarta; Nadia Arsita; Nabilla Mulya Kurniawan; Fallery Setyaprawira (Pusat Riset dan Inovasi Nasional, 2024)
Intranets have evolved from simple internal communications platforms to sophisticated tools, providing a range of functions from real-time communications to seamless access to critical information. With the breadth of the healthcare landscape and the use of intranets in healthcare. The aim of this research is to find out the role of the intranet in building effective collaboration in health services. This research method uses a theoretical study approach. This theoretical theoretical study is a study based on a theoretical basis based on the results of previous research which becomes a theory. The results of this research can play a role in using intranets in health services because they can speed up and simplify work processes and transactions at the hospital. So that the officers at the hospital can work more effectively and efficiently. Finally, the information produced will be timely and useful. It can be concluded that intranet integration in the healthcare sector is not just about the adoption of technology it is an evolution in the way healthcare is delivered. With this intranet, it can certainly provide more targeted, efficient and effective accessibility to patients. For health services, it is necessary to improve health services through the use of intranets where the need for intranet technology can play an important role in equalizing health services to remote areas and cities. So that it can effectively improve service quality.